MRNA expression of genes involved in lipid efflux and matrix degradation in occlusive and ectatic atherosclerotic disease. Issue 12 (25th November 2005) - Soumian, S; Gibbs, R; Davies, A; Albrecht, C
Abstract : Background: Atherosclerotic plaque behaviour is influenced by intraplaque inflammation, matrix turnover, and the lipid core volume. Peroxisome proliferator activated receptor γ (PPARγ) modulates atherosclerosis by its anti-inflammatory and anti-protease activity. PPARγ promotes lipid efflux through the liver X receptor α (LXRα) and the ATP binding cassette transporter A1 (ABCA1). Matrix metalloproteinase 9 (MMP-9) and cyclooxygenase 2 (COX-2) are implicated in plaque instability. Aims: To assess the expression of these genes in occlusive and ectatic atherosclerotic disease to determine the relation between genes involved in lipid efflux and matrix degradation. Methods: Carotid endarterectomy specimens from 16 patients and aneurysm tissue from 16 patients undergoing abdominal aortic aneurysm repair were used. Inferior mesenteric arteries from colectomy specimens from 12 patients served as controls. Total RNA was extracted from pulverised tissue and reverse transcribed into cDNA. Quantitative real time polymerase chain reaction (PCR) was performed using fluorescently labelled probes for ABCA1, LXRα, PPARγ, COX-2, and MMP-9 . Results: PPARγ expression was significantly lower in both occlusive and ecstatic atherosclerotic disease (p<0.001), whereas LXRα and ABCA1 expression was significantly increased (p<0.01). MMP-9 expression was significantly increased in diseased tissues (p<0.0001), and values were highest in occlusive disease (p<0.01). The increases in ABCA1 and MMP-9 mRNA were significantly correlated in diseased tissues (p<0.01, r  = 0.71 and r  = 0.78). COX-2 expression was increased in ectatic but low in occlusive disease (p<0.01). Conclusion: This observational study suggests a role for therapeutic upregulation of PPARγ, which could potentially upregulate lipid efflux through ABCA1 and inhibit matrix degradation through inhibition of MMP-9.